Combination of clofarabine, cyclophosphamide, and etoposide for relapsed or refractory childhood and adolescent acute myeloid leukemia. (19th May 2017) - Messinger, Yoav; Boklan, Jessica; Goldberg, John; DuBois, Steven G.; Oesterheld, Javier; Abla, Oussama; Martin, Alissa; Weinstein, Joanna; Hijiya, Nobuko
ABSTRACT: Relapsed/refractory acute myeloid leukemia (AML) has an extremely poor prognosis. We describe 17 children and adolescents with relapsed/refractory AML who received clofarabine, cyclophosphamide, and etoposide. Seven patients (41%) responded: 4 with a complete response (CR); 1 with CR with incomplete platelet recovery; and 2 with a partial response. Additionally, 4 developed hypocellular marrow without evidence of leukemia; 5 patients had resistant disease; and 1 suffered early toxic death. After further therapy including transplantation, 4 patients (24%) are alive without evidence of disease at a median of 60 months. This anthracycline-free regimen may be studied for relapsed or refractory AML, but due to the high risk of marrow aplasia reduced doses of clofarabine and cyclophosphamide should be used.